Karakteristik Film Tipis GaAs yang Ditumbuhkan dengan Metode MOCVD Menggunakan Sumber Metalorganik TDMAAs (Trisdimethylaminoarsenic) - Andi Suhandi; Heri Sutanto; Pepen Arifin; Maman Budiman; Mohamad Barmawi (Jurnal Matematika & Sains, 2005)
Gallium Arsenide (GaAs) film have been grown by Metalorganic Chemical Vapor Deposition (MOCVD) method on Semi Insulating-Gallium Arsenide (SI-GaAs) substrates using of Trisdimethylaminoarsenic (TDMAAs) and Trimethylgallium (TMGa) precursors. The characteristic of GaAs film strongly depends on growth temperature. The best crystallinity quality of film was obtained at growth temperature, V/III ratio, reactor pressure, N2 and H2 dilute are 580 oC, 4.8, 50 torr, 300 sccm, respectively. X-ray diffraction data indicate that the GaAs films grown at 580 oC show epitaxial layer with FWHM on (200) peak of about 0,477o. Hall effect measurement data indicate that the grown layer were p-type semiconductor, with Hall mobility and carrier concentration in the range of 346 cm2/V.s and 3.17 x 1017 cm-3, respectively. The band gap of GaAs films determined by photoluminiscense (PL) measurement was 1,42 eV. This value is same as the band gap of bulk GaAs.